5FU-loaded PCL/Chitosan/Fe3O4 Core-Shell Nanofibers Structure: An Approach to Multi-Mode Anticancer System - Mehdi Hadjianfar; Dariush Semnani; Jaleh Varshosaz; Sajad Mohammadi; Sayed Pedram Rezazadeh Tehrani (Tabriz University of Medical Sciences, 2022)
Purpose: 5-Fluorouracil (5FU) and Fe3O4 nanoparticles were encapsulated in core-shellpolycaprolactone (PCL)/chitosan (CS) nanofibers as a multi-mode anticancer system to studydrug release sustainability. The structure of the core-shell drug delivery system was alsooptimized according to drug release behavior by artificial intelligence.Methods: The core-shell nanofibers were electrospun by a coaxial syringe. Artificial neuralnetwork (ANN) was used for function approximation to estimate release parameters. A geneticalgorithm was then used for optimizing the structure. Chemical assay of the optimized samplewas performed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD),and energy-dispersive X-ray spectroscopy (EDX). vibration sample magnetometer (VSM) testwas conducted to measure the real amount of loaded magnetic nanoparticles. HepG2 cellcytotoxicity was studied and the results for the optimized samples with and without Fe3O4 after72 hours were reported.Results: Feeding ratio of sheath to core and the amount of CS, Fe3O4, and 5FU had a statisticaleffect on nanofibers diameters, which were 300-450 nm. The drug loading efficiency of thesenanofibers was 65-86%. ANN estimated the release parameters with an error of 10%. Thetemperature increased about 5.6°C in the alternative magnetic field (AMF) of 216 kA.m-1~300kHz and 4.8°C in the AMF of 154 kA.m-1~400 kHz after 20 minutes. HepG2 cell cytotoxicityfor the optimized samples with and without Fe3O4 after 72 hours were 39.7% and 38.8%,respectively.Conclusion: Since this core-shell drug release system was more sustainable compared to theblend structure despite the low half-life of 5FU, it is suggested to utilize it as post-surgicalimplants for various cancer treatments such as liver or colorectal cancer in the future. Thissystem is capable of providing chemotherapy and hyperthermia simultaneously.